Atomic layer deposition process of ruthenium, iridium and rhodium thin films - Yeo, Ke Jun (Nanyang Technological University, 2021)
The thin film industry has shown growth in the recent years, as devices become smaller and more powerful. Thin film desposition technique such as Atomic Layer Deposition (ALD) has shown increasing attractiveness in the modern industry. The ability to deposit films with high conformality and uniformity is well sought after.